2021
DOI: 10.17323/1813-8691-2021-25-1-147-164
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking Technology Adoption for a Robust Food Supply Chain: Evidence from Indian Food Processing Sector

Abstract: This paper pioneers the identification of artificial intelligence (AI) enablers like technology feasibility, sophistication, data integrity, interoperability and perceived benefits that can boost operational efficiency of firms in Indian food processing industry. With the food processing industry contributing significantly to domestic gross value added and generating an export earning of close to USD 40 billion from agricultural and processed food exports, the study examines the role of AI in overcoming the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…Additionally, the finding is supported by the studies of Braunscheidel and Suresh (2009), Ramos et al (2021), Shukor et al (2021), and Yu et al (2018), where the authors identified the importance of collaboration between SCMPs (i.e., strategic supplier partnership, customer relationship management practices, level of information sharing, quality of information sharing) in enhancing overall organizational flexibility, and Cagliano and Mangano (2021), Hazen et al (2016), Jain et al (2021), and Yang et al (2021) confirmed the positive relationship between SCMPs (i.e., strategic supplier partnership, customer relationship management practices, level of information sharing, quality of information sharing) and technology adoption, thus, several studies revealed the importance of SCMPs and technology adoption in enhancing performance of organization. Thus, MSMEs should adopt new technologies to enhance relationship with practices of SCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the finding is supported by the studies of Braunscheidel and Suresh (2009), Ramos et al (2021), Shukor et al (2021), and Yu et al (2018), where the authors identified the importance of collaboration between SCMPs (i.e., strategic supplier partnership, customer relationship management practices, level of information sharing, quality of information sharing) in enhancing overall organizational flexibility, and Cagliano and Mangano (2021), Hazen et al (2016), Jain et al (2021), and Yang et al (2021) confirmed the positive relationship between SCMPs (i.e., strategic supplier partnership, customer relationship management practices, level of information sharing, quality of information sharing) and technology adoption, thus, several studies revealed the importance of SCMPs and technology adoption in enhancing performance of organization. Thus, MSMEs should adopt new technologies to enhance relationship with practices of SCM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies illustrated the importance of technological adoption to collaborate all SC partners (Hazen et al, 2016). Moreover, the integration and collaboration between SC partners (suppliers and customers) can be enhanced through adoption of technologies which facilitates the transformation and exchange of information along SCM processes and overcome SC barriers (Cagliano & Mangano, 2021; Jain et al, 2021; Yang et al, 2021). However, there is limited studies that investigate the link between supply chain management practices and technology adoption.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In the context of agri-food SMEs, studies are also fragmented, and can be focused on phases of technology assimilation (e.g. Ibrahim et al, 2017;Jain et al, 2021), or business model innovation aspects (e.g. Bivona and Cruz, 2021;Dagevos and Lauwere, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Traceability [9,14,15] Food safety and security [14,16] Know-how transfer [5,14,[17][18][19][20] Information sharing [19,20] Logistics Networking [13,[21][22][23][24] Risk mitigation [24,25] Responsiveness [25][26][27][28] Employee Commitment [29,30] Innovation [31][32][33] Managerial Approaches [34,35] After the production stage of food supply chains, the processing stage is another critical stage for sustainable food supply chains [18]. The majority of losses in food supply chains come from the processing stage [14].…”
Section: Factors Authorsmentioning
confidence: 99%
“…Since food supply chains covers vulnerable products, the distribution stage is critical for sustainable food supply chains [13][14][15][16][17][18][19][20][21]. Dependant on food type, distribution routes, networks or vehicle conditions may change [22].…”
Section: Factors Authorsmentioning
confidence: 99%